Mutakheir Al’alfaz by Ibn Faris (Semantic Study) - Al-Mousa, Yasmeen (Dirasat: Human and Social Sciences, 2023)
This research is based on a deep belief in the importance of explaining the semantic aspects abounded by the text of our linguistic heritage books, in the context of forming an integrated series in the semantic Arab lesson system, as this research seeks to reformulate the efforts of Arab scholars to establish the semantic theory through the study of the glossary (Mutakhier Al’alfaz) Ibn Faris semantic, highlighting his efforts in determining the semantics of words and the extent of his success in building and classifying semantics and clarifying semantics between the words of the one section. Despite the abundance of Arab lexical heritage and its diversity and the primacy of Arabs in it, especially in the field of authorship in glossaries of meanings, this heritage is still in great need of those entrusting its findings in search and scrutiny to occupy the position it deserves in the global lexical and semantic study and to complement these efforts made in this Track.